2017
DOI: 10.3889/oamjms.2017.175
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Interleukin-6 (174G/C) Gene Polymorphism on Obesity in Egyptian Children

Abstract: BACKGROUND:Obesity is a multi-factorial chronic disorder. A considerable number of studies have been performed to figure out whether there is an association between obesity and polymorphisms of gene IL-6 (174G/C), but the results are equivocal.AIM:This study aimed to find out whether the IL-6 (174G/C) gene was associated with the risk of developing obesity in Egyptian children.SUBJECTS AND METHODS:The study included 149 children and adolescents with age ranged between 9.5 – 18 years. Eighty-five of them were o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 14 publications
2
9
0
3
Order By: Relevance
“…On correlating the IL-6 levels to the genotypes, no significant difference in IL-6 concentration among different genotypes in both study groups. These results are similar to a study performed on Egyptian obese children which reported also that the IL-6 concentration was independent of -174 G/C in all study subjects [26]. Other studies also support this finding [27,28].…”
Section: Serum Levels Of Serum Il-6supporting
confidence: 91%
“…On correlating the IL-6 levels to the genotypes, no significant difference in IL-6 concentration among different genotypes in both study groups. These results are similar to a study performed on Egyptian obese children which reported also that the IL-6 concentration was independent of -174 G/C in all study subjects [26]. Other studies also support this finding [27,28].…”
Section: Serum Levels Of Serum Il-6supporting
confidence: 91%
“…Both positive and negative associations between obesity and IL-6 polymorphisms in multiple loci have been reported [3,[18][19][20][21][22]. Our study, reporting the lack of a relationship between obesity parameters (BMI and fat%) and IL-6 polymorphisms rs1800795, rs1800796 and rs13306435 in a homogenous population poses an additional voice in this discussion.…”
Section: Discussionmentioning
confidence: 48%
“…A recent study with post‐menopausal female with osteoporosis illustrated that the reduction of estradiol concentration causes a rise in the activity of IL‐1β, IL‐6 and TNF‐α, 34 and it could happen with patients in the studies. Some polymorphisms are associated with the IL‐6 gene, one of them is −174 G/C rs1800795 that is located in promoter region 35 . This polymorphism affects the constitutive transcription of the interleukin gene by controlling the production 36 .…”
Section: Discussionmentioning
confidence: 99%